2015
DOI: 10.1016/j.toxlet.2015.08.657
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the endoperoxide ascaridole modulates its sensitizing capacity

Abstract: The monoterpene ascaridole, a fairly stable endoperoxide found in essential oils such as tea tree oil can provoke allergic contact dermatitis which has been evidenced under patch test conditions. However, concomitantly we observed irritative skin reactions that demand further data underlining the sensitization potential of ascaridole. Here, we studied the effects of ascaridole on dendritic cell (DC) activation and protein reactivity, 2 key steps of chemical-induced skin sensitization. Treatment of human monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Car, Caryo, and Asc showed antileishmanial activity, although they were less selective for Leishmania in comparison with mammalian host cells than EO for Leishmania compared with effects on mammalian host cells (Monzote et al, ; Monzote, Garcia, et al, ). Asc, which is also present in tea tree oil, demonstrated a skin‐sensitizing effect in mammals (Chittiboyina, Avonto, & Khan, ; Krutz et al, ). By the use of iron chelators, it was shown that activation of the endoperoxide Asc in EO by iron is essential for its antiparasitic actions.…”
Section: Introductionmentioning
confidence: 99%
“…Car, Caryo, and Asc showed antileishmanial activity, although they were less selective for Leishmania in comparison with mammalian host cells than EO for Leishmania compared with effects on mammalian host cells (Monzote et al, ; Monzote, Garcia, et al, ). Asc, which is also present in tea tree oil, demonstrated a skin‐sensitizing effect in mammals (Chittiboyina, Avonto, & Khan, ; Krutz et al, ). By the use of iron chelators, it was shown that activation of the endoperoxide Asc in EO by iron is essential for its antiparasitic actions.…”
Section: Introductionmentioning
confidence: 99%